Virtual model testing method for deepwater floating system. (15th December 2022) - Li, Xu; Wei, Handi; Xiao, Longfei; Peng, Tao; Li, Yan; Liu, Jing
Abstract: A virtual model testing method for deepwater floating system is proposed. Viscous factors on platform are taken into account based on the inverse reconstruction of the environmental loads from the measurements in physical experiment with a horizontal mooring system. A pre-offset method is used in the design of the horizontal mooring system to make its horizontal offset range consistent with that of the full-depth mooring system. Finally, numerical calculation is conducted to obtain the hydrodynamic responses using the reconstructed environmental loads and full-depth mooring system. Wave basin tests are performed on a semi-submersible platform using both horizontal and full-depth mooring systems to validate the proposed method. The proposed method can reliably predict the time histories, statistics, and power distribution of surge, heave, pitch motions, and line tensions in head waves, as well as properly predict the flow-induced responses. Further, compared with the conventional hybrid model tests, it can simplify the experimental process and reduce dependence on the space of the wave basin. Highlights: A virtual model testing method for deepwater floating system is proposed. Viscous factors are taken into account based on the inverse reconstruction of the environmental loads from the measurements. A pre-offset method is used in the design of the horizontal mooring system. The feasibility of the proposed method is validated by experimental results.